191 Historical racial residential segregation and present-day social vulnerability in the United States. (20th November 2022) - Ogunmayowa, Oluwatosin; Baker, Charlotte
Abstract : Background: Historical racial residential segregation and higher neighborhood social vulnerability both increase the prevalence of poor health outcomes and behaviors; however, our understanding of how historical residential segregation influences present-day neighborhood social vulnerability is limited. Aims: We assessed whether: 1) historical residential segregation is associated with present-day neighborhood social vulnerability in the U.S., 2) the influence of historical residential segregation on present-day neighborhood vulnerability varied across U.S. cities, and 3) variation in the relationships across cities is due to historical change in educational attainment. Methods: We obtained the 1930s Home Owners' Loan Corporation (HOLC) residential security map of segregation and 2018 U.S. CDC Social Vulnerability Index (SVI) data to analyze our study aims. Results: Using multilevel models, we found significant association between HOLC security risk grades of neighborhoods and all present-day SVI. Neighborhoods formerly assigned less favorable grades by HOLC in the 1930s showed significantly greater vulnerability presently than those that were graded more favorably (i.e., 'D' > 'C' > 'B' > 'A'). Also, we found that the relationship between HOLC security grades and present-day neighborhood SVI varied by city and that the variation in the relationship was explained by change in educational attainment in cities between 1940 and 2018. Neighborhood vulnerability scores in all HOLC delineated neighborhoods decreased as the proportion of adults with no high school diploma decreased in U.S. cities between 1940 and 2018. Conclusion: This study indicates that structural racism creates circumstances that weaken the resilience of communities to external stresses (e.g., injury) on their health.